2019
DOI: 10.1021/acs.langmuir.9b02043
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Enhanced Dissolution of Silica and Alumina in Alkaline Environments

Abstract: Dissolution of mineral surfaces at asymmetric solid–liquid–solid interfaces in aqueous solutions occurs in technologically relevant processes, such as chemical/mechanical polishing (CMP) for semiconductor fabrication, formation and corrosion of structural materials, and crystallization of materials relevant to heterogeneous catalysis or drug delivery. In some such processes, materials at confined interfaces exhibit dissolution rates that are orders of magnitude larger than dissolution rates of isolated surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 66 publications
(100 reference statements)
2
9
0
Order By: Relevance
“…6(a)]. Such an enhanced dissolution was reported in a recent experiment, which showed that the dissolution rates of silica and alumina were increased by up to 2 orders of magnitude over the dissolution rates of isolated compositionally similar surfaces under otherwise identical conditions when the surface electrochemical properties were changed either by an applied potential or close to a dissimilar surface [180]. In addition, similar experimental results were also reported at interfaces between oxides and a metal [181].…”
Section: Implications From Nature: Partition Coefficient Of Element Bsupporting
confidence: 80%
“…6(a)]. Such an enhanced dissolution was reported in a recent experiment, which showed that the dissolution rates of silica and alumina were increased by up to 2 orders of magnitude over the dissolution rates of isolated compositionally similar surfaces under otherwise identical conditions when the surface electrochemical properties were changed either by an applied potential or close to a dissimilar surface [180]. In addition, similar experimental results were also reported at interfaces between oxides and a metal [181].…”
Section: Implications From Nature: Partition Coefficient Of Element Bsupporting
confidence: 80%
“…A previous study has shown that the ion adsorption rate on solute surfaces is affected by electric potential, especially for conductive materials . On the other hand, counterion sorption to mineral surfaces has been observed to induce changes in mineral dissolution rates by up to 1 order of magnitude. , Besides ion adsorption, applying an electric potential within an electrolytic solution could also increase the rate of ion transport, especially at interfaces, which could affect mineral dissolution rates. , Herein, significant enhancements in dissolution rates when a potential is applied, e.g., for calcite, are observedunder isothermal conditionsonly under conditions of mass transport (pH 4) and mixed kinetic control (pH 6.5) ,, but not when dissolution is interface-controlled (pH 10). , Significantly, the recent work of Dobbs et al shows that electric potential has limited, if any, effect on bulk dissolution rates (i.e., at large surface-to-surface separations when the EDLs of neighboring solute surfaces do not interact) under surface-controlled conditions. This may suggest that an applied potential has a greater influence on ion transport than on ion adsorption, thus affecting mineral dissolution rates only under conditions of mass-transport control …”
Section: Resultsmentioning
confidence: 99%
“…The rates and mechanisms of calcite’s dissolution are strongly affected by the solvent’s pH, solution saturation state, the abundance and type of co-ions present in solution, and its ionic strength and temperature. While the vast majority of studies have examined passive approaches for affecting mineral dissolution rates, less is known, for example, of how active stimulation as induced by an electric field may affect dissolution behavior. Some studies have shown how electric potential-induced acidification of the solvent in the proximity of the anode can enhance calcite’s (and other mineral’s) dissolution rates. , Other than the pioneering studies of Kristiansen et al and Dobbs et al, comparatively less is known, however, of how potential-induced ion transport and changes in the structure of the electric double layer (EDL) that is present at the mineral–water interface may affect mineral dissolution, particularly at subcritical potentials (i.e., at ambient temperatures, water dissociates for Δ V ≥ 1.23 V), wherein water’s acidification can be excluded.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Steinwinder & Beckingham, 2019) reported that the mineral dissolution can significantly change the porosity and permeability of the wellbore. Moreover, several studies have found that silica dissolution is closely related to the pH of the solution, as the alkaline solutions are the main cause of dissolving high portions of silica ions due to the high pH (above 9) promoted around the wellbore, resulting in the dissolution of quartz Arensdorf et al, 2010;Dobbs et al, 2019;A. K. Elraies et al, 2016).…”
Section: Introductionmentioning
confidence: 99%